ANALISIS PENGEMBANGAN MODEL BISNIS “HANIFFA KOST” DENGAN PENDEKATAN BUSINESS MODEL CANVAS - Ramadhan, Lalu Daffa Yuza; Agustina, Tri Siwi (Jurnal Riset Entrepreneurship, 2024)
This research aims to analyze and develop the Haniffa Kost management model with the goal of identifying effective solutions to address existing problems and improve service quality for customers. Additionally, the study examines whether the Haniffa Kost business model requires adjustments using the latest Business Model Canvas and Lean Canvas after applying competitor analysis and SWOT analysis concepts. Furthermore, the approach used is qualitative with a descriptive approach. The research findings identify various key elements in the Haniffa Kost business model that need to be maintained or developed. Firstly, the market segment should remain focused on students and working professionals studying or working around the boarding house location, while innovation and diversification are crucial aspects to maintain Haniffa Kost's appeal and relevance. Developing capacity and facilities are important steps to meet growing demand, and social media communication is an effective way to market boarding house services. Improving service quality and sustaining innovation are key to maintaining competitive advantage. Additionally, the research designs relevant recommendations for changes to the Haniffa Kost business model.